2013
DOI: 10.1111/jdv.12307
|View full text |Cite
|
Sign up to set email alerts
|

The risk of herpes zoster during biological therapy for psoriasis and other inflammatory conditions

Abstract: Recent advances in biological therapies have proved highly effective in treating psoriasis and other inflammatory conditions, including psoriatic arthritis, rheumatoid arthritis, inflammatory bowel disease and ankylosing spondylitis. However, adverse effects related to their immunosuppression have been observed, including an increased propensity to viral infections. This review evaluates the evidence of herpes zoster (HZ) risk from biologics based on clinical reports, cohort studies and randomized controlled s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 59 publications
3
49
0
5
Order By: Relevance
“…The pathophysiology of psoriasis includes Th17 cell and Th1 cell lymphocyte activity, increased activity of antigen-presenting cells, production of inflammatory cytokines, epidermal hyperproliferation and angiogenesis [22]. IL-17 is a principal effector of Th17 cell.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology of psoriasis includes Th17 cell and Th1 cell lymphocyte activity, increased activity of antigen-presenting cells, production of inflammatory cytokines, epidermal hyperproliferation and angiogenesis [22]. IL-17 is a principal effector of Th17 cell.…”
Section: Discussionmentioning
confidence: 99%
“…En fait, le risque de zona serait différent en fonction des biomédicaments. L'infliximab semblerait être l'anti-TNF le plus à risque pour le développement du zona [19,20,22,26,27]. Cependant, là encore, les études sont contradictoires.…”
Section: Incidence Sous Biomédicamentsunclassified
“…Zhang et al reported that zoster vaccination was not related to increased risk of HZ in patients with immune-mediated disease including psoriasis under biological therapy [25,26]. However, it was emphasized that infliximab increases the risk of HZ in most of the cohort studies while the risk of HZ in patients receiving etanercept, adalimumab or ustekinumab therapy is not clear [27]. Yun et al indicated that the use of biologic agents and systemic steroids in patients with autoimmune and inflammatory diseases increased the risk of HZ [28].…”
Section: Inactivated or Inert Vaccines Live Vaccinesmentioning
confidence: 99%
“…Consequently, HZ vaccination should be considered for patients who are going to receive biological agents especially infliximab and combination treatment with MTX therapy. Additionally, the vaccine should be administered before initiation of the immunosuppressive therapy [24,27].…”
Section: Inactivated or Inert Vaccines Live Vaccinesmentioning
confidence: 99%